Transforming Learning Landscapes: A Critical Analysis of Emerging Pedagogical Trends in the Post-NEP Era - Dr. Yad Ram, (International Journal of Advanced Research and Multidisciplinary Trends (IJARMT), 2025)
Education is supposed to prepare a person for life by giving him the physical, mental, emotional, and spiritual tools he needs to face life's obstacles with confidence, boldness, making the right choices, and widening his horizons. The main goal of education is to help people live meaningful and practical lives. The disparity in educational quality, which tends to be a reflection of prosperity, is one of the main issues facing the current educational system. The National Education Policy 2020 (NEP 2020), which promotes a learner-centered, flexible, multidisciplinary, and technology-enabled pedagogy that shifts away from rote memorization toward critical thinking, creativity, and lifelong learning, has significantly changed India's educational landscape in recent years. (Gandhi, 2023, pp. 3-5) The study offers a critical analysis of the new pedagogical trends in the post-NEP era, looking at how curriculum structure modifications (like the 5+3+3+4 model), the incorporation of inquiry-based and experiential learning, and the use of digital tools are changing student engagement, teacher practice, and institutional frameworks. Additionally, the study examines how this vision is being matched with teacher professional development, inclusive pedagogy, multilingual instruction, and assessment reforms, as well as what obstacles still need to be overcome to balance policy goals with practical implementation. (Bhoi, & Patra, 2023, pp. 10-12) The study identifies important facilitators and impediments to changing learning environments through a qualitative synthesis of literature, policy papers, and empirical findings. These include systemic limitations, infrastructure preparation, and teacher preparedness. The results indicate that although the NEP 2020 offers a daring pedagogical innovation roadmap, its success depends on significant capacity building, contextual adaptation, ongoing institutional support, and ongoing monitoring. In order to accelerate and deepen the transition of pedagogy in Indian schools in ways that are equitable, contextualized, and sustainable, the study ends with recommendations for education stakeholders.